Nature-based solutions for climate adaptation in small island developing states: a systematic review - Brown, Zoe; Kendall, Katrina; O’Donnell, Emma; Tavasi, Leah; Seddon, Nathalie (Frontiers in Environmental Science, 2026)
IntroductionSmall Island Developing States (SIDS) are disproportionately affected by climate change, with impacts threatening their communities, ecosystems, and economies. Nature-based solutions (NbS) offer a promising approach to address these challenges, yet their effectiveness in SIDS remains poorly understood.MethodsWe systematically reviewed 49 studies reporting 53 NbS interventions across 26 SIDS, coding intervention types, ecosystems, climate hazards, adaptation effectiveness, broader outcomes (social, ecological, economic, mitigation), and reported socio-ecological resilience mechanisms.ResultsNearly three-quarters of cases reported positive climate outcomes, though only half provided clear evidence, and fewer employed baselines, counterfactuals, or thresholds. Evidence was skewed toward croplands and agroforestry, while coastal ecosystems were underrepresented. Broader outcomes were mostly positive, but reporting on ecological and social resilience mechanisms was limited, equity considerations were largely absent, and formal economic appraisals and direct comparisons with non-NbS alternatives were scarce. Large geographic gaps were also evident, with more than half of SIDS unrepresented in the literature.DiscussionOverall, the evidence indicates that NbS can reduce climate risks in SIDS and deliver ‘triple wins’ for climate, biodiversity, and people, but decision confidence is constrained by uneven geographic coverage, agricultural bias, lack of counterfactuals and baselines, limited equity reporting, and scarce economic appraisal. Future research priorities include: (1) stronger representation of under-studied SIDS contexts, (2) greater focus on coastal and ocean-related NbS, (3) evidence linked to baselines and counterfactuals, (4) holistic, long-term monitoring and evaluation, (5) national- and regional-scale synthesis of grey literature, and (6) integration of equity and knowledge pluralism in NbS design and evaluation. These steps would help governments design, finance, and account for high-integrity NbS in NDCs, NAPs, adaptation investment plans, and disaster-risk strategies.Systematic Review Registrationhttps://osf.io/wcb68, identifier wcb68.